2006
DOI: 10.1115/1.2375125
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms Affecting Fluidic Vectoring Using Suction

Abstract: Suction was applied asymmetrically to the exhaust of a rectangular subsonic jet creating a pressure field capable of vectoring the primary flow at angles up to 15deg. The suction simultaneously creates low pressures near the jet exhaust and conditions capable of drawing a secondary flow along the jet shear layer in the direction opposite to the primary jet. This countercurrent shear layer is affected both by the magnitude of the suction source as well as the proximity of an adjacent surface onto which the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The lateral force caused by the bi-stable asymmetric forebody vortices at a high angle of attack can be estimated by the circumferential pressure distribution [24]. Regarding FTVC technology, previous studies have indicated that the vectoring angle of FTVC is strongly determined by the near-wall pressure on both sides of the jet [25][26][27]; therefore, it is possible to estimate the thrust vectoring properties through the wall pressure distribution. Normally, a dense array of pressure sensors on the nozzle wall is always required to obtain the pressure distribution on the wall, but this solution is impractical for in-flight applications.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral force caused by the bi-stable asymmetric forebody vortices at a high angle of attack can be estimated by the circumferential pressure distribution [24]. Regarding FTVC technology, previous studies have indicated that the vectoring angle of FTVC is strongly determined by the near-wall pressure on both sides of the jet [25][26][27]; therefore, it is possible to estimate the thrust vectoring properties through the wall pressure distribution. Normally, a dense array of pressure sensors on the nozzle wall is always required to obtain the pressure distribution on the wall, but this solution is impractical for in-flight applications.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Gillgrist et al [15] used particle image velocimetry and conventional pressure sensors to obtain the results of the transient velocity field. The Reynolds stress field of the near−wall flow under the stable control state for the reverse flow vectoring nozzle model demonstrated that the lateral pressure gradient generated by the negative suction pressure and the reverse flow shear layer, under the combined action of the induced negative pressure on the wall, is the cause of the jet vector deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidic thrust vectoring control technology will soon become a new direction of thrust vector technology development. 11,12 According to the generation principle of thrust vector, the realization forms of fluid thrust vector control technology can be roughly divided into five basic types: shock vector fluid thrust vector control, Throat Skewing fluid thrust vector control, counter-flow fluid thrust vector control, Co-flow fluid thrust vector control and Coanda effect fluid thrust vector control. 7,8,[12][13][14][15] The shock vector control is to introduce a secondary jet into one side of the nozzle expansion section, and generate oblique shock when the high-speed main stream flows through it, so as to change the direction of the main stream to obtain the required vector angle.…”
Section: Introductionmentioning
confidence: 99%
“…Fluidic thrust vectoring control technology will soon become a new direction of thrust vector technology development. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%